2021
DOI: 10.1002/adfm.202102442
|View full text |Cite
|
Sign up to set email alerts
|

Ambilaterality of Redox Mediators towards 1O2 in Li‐O2 Batteries: Trap and Quencher

Abstract: Lithium oxygen batteries (LOBs) are considered promising next‐generation lithium batteries owing to their high theoretical specific energy density. However, several issues must be addressed for realizing the practical applications of LOBs. Among them, the evolution of singlet oxygen (1O2)—which undergoes vigorous reactions that compromise the stability of the system—is a key challenge. The high overpotential induced by low‐conductivity lithium peroxide necessitates the use of a redox mediator (RM) to facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Both TDPA and TPA-CH 3 possess excellent quenching effect, mainly because of the robust and electron-rich structure of tertiary amine with three phenyl groups. Conversely, the unsatisfactory chemical stability of DABCO limits its quenching effect in battery systems ( 23 , 24 ), resulting in low quenching efficiency of 65.6%. In general, robust and electron-rich chemicals own universal 1 O 2 quenching effect for Li-O 2 battery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both TDPA and TPA-CH 3 possess excellent quenching effect, mainly because of the robust and electron-rich structure of tertiary amine with three phenyl groups. Conversely, the unsatisfactory chemical stability of DABCO limits its quenching effect in battery systems ( 23 , 24 ), resulting in low quenching efficiency of 65.6%. In general, robust and electron-rich chemicals own universal 1 O 2 quenching effect for Li-O 2 battery.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, electron-rich quenchers are able to accelerate the decay of 1 O 2 to the ground-state triplet oxygen ( 3 O 2 ) and restrain the harmful 1 O 2 -related side reactions ( 22 ). However, most adopted quenchers, such as organic amines, radical molecules, and redox mediators (RMs), are limited by their electrochemical irreversibility, insufficient chemical stability and low quenching efficiencies ( 23 ). For instance, 1,4-diazabicyclo[2.2.2]octane (DABCO) and RM of 5,10-dimethylphenazine (DMPZ) have manifested modest quenching efficiencies, but they are hindered by the electrochemical irreversibility and moderate chemical stability against 1 O 2 , respectively ( 24 26 ).…”
mentioning
confidence: 99%
“…A number of soluble redox mediators (RM) have been proposed: tetrathiafulvalene (TTF/TTF + ), [41][42][43] LiI 44 and triiodide (I 3 − /I − ), 45 LiBr, 46 ethyl viologen, [47][48][49] 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO), 50 2-azaadamantane-N-oxyl (AZADO), 51 5,10-dimethylphenazine (DMPZ) 52 and tris [4-(diethylamino)phenyl] amine (TDPA), 53 as reviewed by Kwak. 54 Dual mediators for catalysis of the O 2 reduction and the Li 2 O 2 oxidation have been tried, i.e. 2,5-di-tert-butyl-1,4benzoquinone (DBBQ) on discharge and TEMPO on charge, 38 ethyl viologen combined with LiI, 55 and a bifunctional soluble Fe phtalocyanine 56,57 that shuttles electrons both in the cathodic and anodic reactions have also been considered.…”
Section: Redox Mediators and 1 O 2 Quenchersmentioning
confidence: 99%
“…1 O 2 can not only decompose cell components but also deactivate redox mediators (RMs). [44,45] As we found that 1 O 2 evolution was accelerated by the T-C-mediated disproportionation reaction, it is necessary to check whether the SODm itself is degraded by 1…”
Section: Stability Of Additives Against 1 Omentioning
confidence: 99%